Resilience and precarious success. (September 2015) - Patterson, Mary D; Wears, Robert L
Abstract: This paper presents an empirical case study to illustrate, corroborate, and perhaps extend some key generalizations about resilient performance in complex adaptive systems. The setting is a pediatric hematology/oncology pharmacy, a complex system embedded in the larger complex of the hospital, which provides chemotherapy and other high risk medications to children with cancer, sickle cell disease and autoimmune disorders. Recently the demands placed on this system have dramatically intensified while the resources allocated to the system have remained static. We describe the adaptations of this system in response to this additional stress. In addition, we discuss the risks associated with miscalibration about the system׳s adaptive capacity, and the tradeoff between the need to invest in adaptive capacity (to sustain performance when the system is stressed) versus the need to invest in efficient production (to sustain performance under normal circumstances and economic pressures). Highlights: We describe a complex adaptive system: a pediatric hematology/oncology pharmacy. Work in this system has changed and intensified, but resources have remained static. Staff׳s adaptive behaviors demonstrate graceful extensibility and fluency. The HO staff has demonstrated extraordinary adaptive behaviors. Leadership miscalibrates the efforts required to perform the pharmacy׳s work.